WIRELESS OFFSHORE PLATFORM STRUCTURAL HEALTH MONITORING - ELDIN MOHAMED, AHMED MOHAMED GAMAL (Universiti Teknologi Petronas, 2013)
Oil platforms are known for their operation in dangerous environments. The most recent technology adapted is the unmanned platform which is a remotely operated platform without any workers on the platform during the operation to lessen the losses occurs in the platforms. To ensure the safety and the reliability of the new platforms a safety monitoring system is required to be developed. In this report, a new structural health and safety monitoring system for unmanned platforms is proposed and developed. The objectives of the project are to develop a system which processes electrical signals to represent structural parameters, develop the proper communication between different parts of the system and test the feasibility of the system. The new system integrates microprocessor technologies and communication technologies to meet the objectives of the proposed system. The project focused on testing the proper connection between the microprocessor and the measuring devices, and studying and simulating the wireless and underwater communication. The system was tested using strain gages to measure strain and half-cell to measure corrosion. The readings obtained were validated against commercial acquisition systems. The results show the efficiency of the system in different applications to measure different structural parameters. The underwater transmission was simulated using OMNET++. The simulation results show low efficiency of acoustic communication which requires further study and investigation.